An overview of effective factors on consumer behavior intentions toward choosing environmental friendly hotels in Malaysia - Moghadas, Shayesteh; Nezakati, Hossein *; Yuhanis, Binti Abdul (2015)
Concerns related to the environment are evident in the increasingly ecologically aware marketplace. One the competititive advantages of hotels is a green management as long as the increasingly concerns about the environmental issue and playing an importamt role in this industry .In Malaysia one of the important factors has effect on economy and also helping to achieving the plan of 2020 is increasing the number of tourists. This study is reviewing the factors which influence on consumer attitudes and behavior intentions based on Theory of Planned Behavior (TPB) and also marketing mix tools toward choosing green practices in lodging industry focused on green hotels in Malaysia. The research methodology is based on secondary data and the purpose of that is trying to understand TPB factors and marketing mix in hospitality sector focused on environmental friendly hotels in Malaysia. Findings of this study contribute to researchers, hotel managers and policy makers in tourism industry especially in environmental friendly hotels in Malaysia. Keywords: Environmental Friendly Hotel, Green practice, Consumer Behavior Intention